An analysis of school dropout in Mozambique, 2014-15 - Félix Mambo; Maren Basso; Vincenzo Salvucci; Ricardo Santos (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
The level of educational attainment in Mozambique is one of the lowest in the world and primary school completion rate is also very low, not reaching 40 per cent. Using data from the Mozambican Household Budget Survey 2014/15, we study (1) the determinants of school dropout; (2) the variables that are associated with school dropout in the year of the survey, exploiting its panel structure; and (3) infrastructural or social protection interventions in rural villages that can influence dropout, using a propensity score matching analysis. We find that age, child labour, household head's gender and education, and access to services are particularly associated with the probability of dropout, and that early marriage and teen pregnancy are consistently associated with higher dropout rates. Our results also suggest that building or renovating a school or a water facility, or setting up a social protection programme can reduce the probability of dropout. This can be of support to the redesign of the country's education, infrastructural, and social protection policies, especially in rural areas.
Keywords: I21; I28; 330; Mozambique; panel regression; propensity score matching; school dropout determinants